Prevalence and risk factors associated with sexually transmitted infections (STIs) among women of reproductive age in Swaziland - Ginindza, TG; Stefan, CD; Tsoka-Gwegweni, JM; Dlamini, X; Jolly, PE; Weiderpass, E; Broutet, N; Sartorius, B (BioMed Central, 2017)
Background Sexually transmitted infections (STIs) remain an important public health problem with approximately half a billion new cases annually among persons aged 15–49 years. Epidemiological data on STIs among women of reproductive age in Swaziland are limited. The availability of epidemiological data on STIs and associated risk factors in this population is essential for the development of successful prevention, diagnosis and management strategies in the country. The study aimed to determine the prevalence and risk factors associated with STIs. Methods A total of 655 women aged 15–49 years were systematically enrolled from five health facilities using a cross-sectional study design. Cervical specimen were tested using GeneXpert CT/NG Assays for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG), GeneXpertTV Assay for Trichomonas vaginalis (TV), and GeneXpert HPV Assays for hr-HPV. Blood samples were tested using Alere Determine HIV-1/2Ag/Ab Combo and Trinity Biotech Uni-Gold Recombigen HIV test for confirmation for HIV, and Rapid Plasma Reagin and TPHA test for confirmation for Treponema pallidum (syphilis). Genital warts were assessed prior to specimen collection. Survey weighted analyses were done to estimate the population burden of STIs. Results The four most common curable STIs: CT, NG, TV, Treponema pallidum (syphilis), as well as genital warts were considered in this study. The overall weighted prevalence of any of these five STIs was 19.4% (95% CI: 14.9–24.8), corresponding to 72 990 women with STIs in Swaziland. The estimated prevalences were 7.0% (95% CI: 4.1–11.2) for CT, 6.0% (95% CI: 3.8–8.8) for NG, 8.4% (95% CI: 5.4–12.8) for TV, 1.4% (95% CI: 1.1–10.2) for syphilis and 2.0% (95% CI: 1.0–11.4) for genital warts. The overall weighted HIV prevalence was 42.7% (95%CI: 35.7–46.2). Among hr-HPV positive women, 18.8% (95% CI: 13.1–26.3) had one STI, while 6.3% (95% CI: 3.3–11.7) had multiple STIs. Risk factors associated with STIs were being employed (OR = 2.2, 95% CI: 1.0–4.7), self-employed (OR = 2.8, 95% CI: 1.5–5.5) and being hr-HPV positive (OR = 2.0, 95% CI: 1.3–3.1). Age (0.9, 95% CI: 0.8–0.9), being married (OR = 0.4, 95% CI: 0.3–0.7) and not using condoms with regular partners (OR = 0.5, 95% CI: 0.3–0.9) were inversely associated with STIs. Conclusion STIs are highly prevalent among women of reproductive age in Swaziland. Thus, a comprehensive STIs screening, surveillance and treatment programme would be justified and could potentially lower the burden of STIs in the country.